COVID-19 Translated Messages: Arabic Speakers’ Acceptability of Lexical Choices (Journal of the College of Languages (JCL), 2022)
Worldwide, there is an increased reliance on COVID-19-related health messages to curb the COVID-19 outbreak. Therefore, it is vital to provide a well-prepared and authentic translation of English-language messages to reach culturally and linguistically diverse audiences. However, few studies, if any, focus on how non-English-speaking readers receive and linguistically accept the lexical choices in the messages translated into their language. The present study tested a sample of translated Arabic COVID-19-related texts that were obtained from the World Health Organization and Australian New South Wales Health websites. This study investigated to that extent Arabic readers would receive translated COVID-19 health messages and whether the translation would affect their preparedness to easily accept and their ability to fully comprehend the messages in terms of the used lexical items. The survey-based research also explored the translation process and methods that would best ensure the messages would reach the target audience with the least loss of meaning. The study concluded that some acceptability issues and comprehensibility failure were detected in the available translated versions as a result of improper word selection, which could be attributed to adopting a literal translation method and uncommon collocations of certain medical terminologies. Therefore, this study recommends that effective translation of COVID-19-related health messages will be achieved by adopting a two-tier translation process, preferably involving a medical specialised translator.